2015
DOI: 10.1002/anie.201500598
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Tobramycins with Immunomodulatory Properties

Abstract: Amphiphilic aminoglycosides (AAGs) are an emerging source of antibacterials to combat infections caused by antibiotic-resistant bacteria. Mode-of-action studies indicate that AAGs predominately target bacterial membranes, thereby leading to depolarization and increased permeability. To assess whether AAGs also induce host-directed immunomodulatory responses, we determined the AAG-dependent induction of cytokines in macrophages in the absence or presence of lipopolysaccharide (LPS). Our results show for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 42 publications
3
41
0
Order By: Relevance
“…Membranes are essential for the viability of all cells and therefore are attractive targets for the development of antibiotics,a lthough very few antimicrobial agents that act by disrupting the microbial cell membrane are in clinical use. [1,2] One of the obstacles to rational design of membrane disrupting agents is the lack of detailed understanding of their mode of action. Unlike many known antimicrobial drugs that act by binding primarily to awell-defined domain in aprotein target, cell disrupting agents can potentially act on numerous sites on the surface and in the cytosol of the microbial cell.…”
mentioning
confidence: 99%
“…Membranes are essential for the viability of all cells and therefore are attractive targets for the development of antibiotics,a lthough very few antimicrobial agents that act by disrupting the microbial cell membrane are in clinical use. [1,2] One of the obstacles to rational design of membrane disrupting agents is the lack of detailed understanding of their mode of action. Unlike many known antimicrobial drugs that act by binding primarily to awell-defined domain in aprotein target, cell disrupting agents can potentially act on numerous sites on the surface and in the cytosol of the microbial cell.…”
mentioning
confidence: 99%
“…[24] Cationic antimicrobial peptides (CAPs) are produced by numerous organisms to combat microbial infections.C APs self-assemble and form pores in the microbesp lasma membrane leading to membrane permeabilization and cell death. [32][33][34][35][36][37][38] Thed esign of these antimicrobial agents is based on the attachment of membrane-anchoring hydrophobic residues to an aminoglycoside scaffold that is positively charged under physiological conditions.Antibiotics from the aminoglycoside class perturb the fidelity of bacterial translation by binding to the decoding A-site region of the bacterial ribosome;h owever, their target site is shifted from the ribosome to the plasma membrane through conjugation to one or more hydrophobic residues. [31] Thec hemical composition principles learned from the study of CAPs have been used to design several types of synthetic membrane-disrupting agents.I nr ecent years,s everal research groups have been engaged in the development of membrane-disrupting cationic amphiphiles derived from aminoglycosides.…”
Section: Targeting the Plasma Membranementioning
confidence: 99%
“…Similarly, amphiphilic aminoglycosides are known to disrupt bacterial membranes . Moreover, we recently reported that some amphiphilic aminoglycosides may possess beneficial immunomodulatory properties . In preliminary work, we recently demonstrated that amphiphilic lysines conjugated to tobramycin strongly synergized minocycline and rifampicin against antibiotic‐resistant P. aeruginosa .…”
Section: Introductionmentioning
confidence: 99%